Bush‐Shaped Vertical Graphene/Nichrome Wire for Blackbody‐Like Radiative Heating. (10th October 2022) - Wang, Kun; Cheng, Shuting; Yang, Jiawei; Cheng, Yi; Ci, Qing; Yuan, Hao; Huang, Kewen; Liu, Ruojuan; Li, Wenjuan; Li, Junliang; Tu, Ce; Liang, Fushun; et al.
Abstract: Radiative thermal management has attracted increasing attention for the advantages of energy saving and carbon emission reduction. Infrared radiation coatings are widely adopted to alleviate the low infrared emissivity of commonly used metal alloy electrothermal materials. However, traditional infrared radiation coatings are faced with the issues of the unsteady waveband emissivity, low interfacial adhesion to substrates, and poor long‐term thermal stability. Herein, a bush‐shaped vertical graphene (BVG) grown on nichrome (Ni–Cr) wire is demonstrated, relying on which BVG/Ni–Cr wire presents a high blackbody‐like emissivity of ≈0.96 across a wide wavelength range (2.5–18 µm). When used for radiative heating, BVG/Ni–Cr wire achieves a high thermal radiation efficiency with an order of magnitude improvement compared with bare Ni–Cr wire, as well as the superior deformation and thermal stabilities. These findings reveal the impressive potentials of BVG as an excellent infrared radiation material for the energy‐efficient radiative thermal management. Abstract : A bush‐shaped vertical graphene (BVG) layer is demonstrated to enhance the infrared radiation property of nichrome (Ni–Cr) wire. The BVG/Ni–Cr wire behaves similarly to a blackbody with the excellent infrared emission properties. When used for radiative heating, BVG/Ni–Cr wire exhibits a high thermal radiation efficiency as well as superior deformation and thermal stabilities.